2022
DOI: 10.1038/s41598-022-09438-9
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer cells shift rapidly and spontaneously to cisplatin-resistant oxidative phosphorylation that is trackable in real time

Abstract: Genetic mutations have long been recognized as drivers of cancer drug resistance, but recent work has defined additional non-genetic mechanisms of plasticity, wherein cancer cells assume a drug resistant phenotype marked by altered epigenetic and transcriptional states. Currently, little is known about the real-time, dynamic nature of this phenotypic shift. Using a bladder cancer model of nongenetic plasticity, we discovered that rapid transition to drug resistance entails upregulation of mitochondrial gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Typically, the concentration of cisplatin used in mammalian cell culture is in the range of 2 μM–100 μM. 52 In our work we used 25 μM cisplatin, as also used in studies by Xu et al , Arany et al , and Mortensen et al 53–55…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the concentration of cisplatin used in mammalian cell culture is in the range of 2 μM–100 μM. 52 In our work we used 25 μM cisplatin, as also used in studies by Xu et al , Arany et al , and Mortensen et al 53–55…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the concentration of cisplatin used in mammalian cell culture is in the range of 2 mM-100 mM. 52 In our work we used 25 mM cisplatin, as also used in studies by Xu et al, Arany et al, and Mortensen et al [53][54][55] A549 cells (at densities ranging from 9 × 10 3 to 5 × 10 4 mL −1 ) were treated with 25 mM of cisplatin for drug studies, and control A549 cells were treated with the vehicle (PBS solution used to dissolve cisplatin) only. We have used low density A549 cells in our SICM imaging studies to enable the selection of an isolated single cell.…”
Section: Treatment Of A549 Cells With Cisplatinmentioning
confidence: 99%
“…In the context of bladder cancer chemotherapy, understanding the evolution of tumor resistance involves integration of spontaneous, drug-induced, and CSCs-related resistance in understanding tumor resistance evolution. Drug-sensitive bladder cancer cells have been found to spontaneously transit to cisplatin-resistant phenotype [19]. Cho et al demonstrated treatment-induced multidrug resistance (MDR) in bladder cancer [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains challenging to apply such information in clinical practice to guide treatment decision-making 59,17 . In addition, drug treatment itself may induce changes in tumor characteristics, such as genetic instability, and cause enrichment of speci c molecular subclones, which may result in altered drug-sensitivity and acquired drug-resistance [17][18][19][20] . Platforms that allow drug-response monitoring longitudinally may therefore have great value in developing personalized and adaptive treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale genetic analyses of bladder cancer have identi ed drivers such as TP53, ARID1A, PIK3CA, FGFR3, STAG2 and ERBB2 and have yielded several molecular classi cation methods 12 , with consensus markers such as TP63 (Transitional/Intermediate cells), KRT5 (Basal class), KRT20 (Luminal class) and UKP3A (Urothelial differentiation) 11,[13][14][15][16] . However, it remains challenging to apply such information in clinical practice to guide treatment decision-making 59,17 . In addition, drug treatment itself may induce changes in tumor characteristics, such as genetic instability, and cause enrichment of speci c molecular subclones, which may result in altered drug-sensitivity and acquired drug-resistance [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%